Investigation of factors related to cyberchondria levels of health management and banking and insurance department students: An empirical analysis - Uslu, Yeter; Aygün, Sefer (Nişantaşı University, 2022)
In recent years, the internet has become a primary source of information and communication on nearly every topic imaginable and health information is no exception. More and more people are turning to the internet for answers regarding their health concerns, and for many, this has turned into an unhealthy obsession. The excessive examination of health information on the internet and the resulting increase in health anxiety has been given the name “cyberchondria”. This study aimed to reveal the effects of health education on the expression of cyberchondria by comparing two undergraduate departments, one of which received health education at the undergraduate level and one of which did not receive health education. A total of 418 participants took part in the study. The T-test and Mann-Whitney-U test were used to evaluate the differences between the two variables, while One-Way Analysis of Variance (ANOVA) and the Kruskal-Wallis test were used to evaluate the differences between three or more variables. The independent variables in this study, which consisted of a range of demographic information, showed no statistically significant difference between the departments. However, when the mean scores of the departments were examined, it was observed that the students who had received health education had lower scores on the Cyberchondria Severity Scale (CSS). This supports the results obtained in some previous studies. As a result, it can be concluded that the availability of accurate and formal health education is an important factor in reducing the levels of cyberchondria.

Son yıllarda internet, sağlık bilgileri de dahil olmak üzere akla gelebilecek hemen hemen her konuda birincil bilgi ve iletişim kaynağı haline gelmiştir. Giderek daha fazla insan sağlık sorunlarıyla ilgili cevaplar için internete yönelmektedir. Birçokları için bu sağlıksız bir saplantıya dönüşebilmektedir. İnternetteki sağlık bilgilerinin gereğinden fazla incelenmesi ve buna bağlı olarak sağlık kaygısının artmasına “siberkondri” adı verilmiştir. Bu çalışma, biri lisans düzeyinde sağlık eğitimi alan ve biri sağlık eğitimi almayan iki lisans bölümünü karşılaştırarak sağlık eğitiminin siberkondrinin üzerindeki etkilerini ortaya koymayı amaçlamıştır. Çalışmada toplam 418 katılımcı yer almıştır. İki değişken arasındaki farkları değerlendirmek için T-testi ve Mann-Whitney-U testi, üç ve daha fazla değişken arasındaki farkları değerlendirmek için Tek Yönlü Varyans Analizi (ANOVA) ve Kruskal-Wallis testi kullanıldı. Bir dizi demografik bilgiden oluşan bu çalışmada bağımsız değişkenler, bölümler arasında istatistiksel olarak anlamlı bir farklılık göstermemiştir. Ancak bölümlerin puan ortalamaları incelendiğinde sağlık eğitimi alan öğrencilerin Siberkondri Şiddet Ölçeği (CSS) puanlarının daha düşük olduğu görülmüştür. Bu, daha önce yapılan bazı çalışmalarda elde edilen sonuçları desteklemektedir. Sonuç olarak sağlık eğitiminin bulunmasının siberkondri düzeylerinin düşürülmesinde önemli bir faktör olduğu sonucuna varılabilir.
Sağlık yönetimi ve bankacılık ve sigortacılık bölümü öğrencilerinin siberkondri düzeyleriyle ilgili faktörlerin incelenmesi: Ampirik bir analiz
Keywords: Cyberchondria; Health Anxiety; Health Education; Online Health Research; Online Research; Siberkondri; Sağlık Kaygısı; Sağlık Eğitimi; Çevrimiçi Sağlık Araştırması; Çevrimiçi Araştırma